A case to examine organisational change. (1st September 2004) - Nevelli, Karen; Mohally, David
The focus of this study is an investigation of the success of change management in supporting the implementation of a large organisational adjustment, in the shape of CRM, across several subsidiaries of a multinational organisation. The study indicates a strong requirement to involve all of the participants and instill a sense of ownership of the challenge throughout the organisation to lessen employee resistance. We conclude that a stepped approach in preparing the organisation's employees is necessary in ensuring that a dramatic change, such as CRM, will be accepted at every level.